Geología de los cuadrángulos de Río Güeppí, Güeppí, Santa Teresa, Puerto Véliz, Pantoja, Río Angusilla, Angusilla, Quebrada Lobo, Vencedores, Chingana, Nueva Jerusalén, Yabuyanos, Bellavista, Arica, San Martín, Río Tamboryacu y Campuya 1-l, 1-m, 1-n, 1-ñ, 2-m, 2-n, 2-ñ, 3-l, 3-m, 3-n, 3-ñ, 3-o, 4-l, 4-m, 4-n, 4-ñ, 4-o – [Boletín A 129] - Cerrón Zeballos, Fredy (1999)
239 p., 17 mapas